1991
DOI: 10.1002/art.1780340403
|View full text |Cite
|
Sign up to set email alerts
|

Serum keratan sulfate. Quantitative and qualitative comparisons in inflammatory versus noninflammatory arthritides

Abstract: The concentration of keratan sulfate (KS) epitope was measured in the serum of patients with osteoarthritis (OA) or rheumatoid arthritis (RA) by enzyme-linked immunosorbent assay and compared with that in the serum of patients with primary fibromyalgia syndrome (PFS) and of controls who had no joint disease. By Student's t-test, the mean serum KS concentrations in OA and RA patients measured with monoclonal antibodies (MAb) 5-D-4 and 2-D-3 were significantly increased over those in the PFS and normal groups; s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

1992
1992
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 22 publications
0
17
1
Order By: Relevance
“…Using antibodies to core protein and KS epitopes on aggrecan, we and others have shown that degradation products can be found in synovial fluids (SF) and sera of patients with a variety of different types of arthritis (21)(22)(23)(24)(25)(26)(27)(28)(29)(30). KS-containing fragments, measured by ELISA, have been shown to be present in increased amounts in the SF, and possibly in the serum, of patients with OA (22)(23)(24)(25), although they may be unchanged or decreased in content in the sera of patients with RA (29,30).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using antibodies to core protein and KS epitopes on aggrecan, we and others have shown that degradation products can be found in synovial fluids (SF) and sera of patients with a variety of different types of arthritis (21)(22)(23)(24)(25)(26)(27)(28)(29)(30). KS-containing fragments, measured by ELISA, have been shown to be present in increased amounts in the SF, and possibly in the serum, of patients with OA (22)(23)(24)(25), although they may be unchanged or decreased in content in the sera of patients with RA (29,30).…”
Section: Introductionmentioning
confidence: 99%
“…KS-containing fragments, measured by ELISA, have been shown to be present in increased amounts in the SF, and possibly in the serum, of patients with OA (22)(23)(24)(25), although they may be unchanged or decreased in content in the sera of patients with RA (29,30). Our previous studies using an immunoassay which detects relatively large PG fragments containing KS (31 ), revealed that there was an inverse correlation between the content of these molecules and the acute phase reactant orosomucoid in the sera of patients with RA (29).…”
Section: Introductionmentioning
confidence: 99%
“…In a variety of joint diseases, the integrity of cartilage matrix is impaired, and the degradative matrix products are released directly into the joint fluid. Although the mechanism by which cartilage metabolites emerge from the joint cavity and enter the circulation is still unclear, levels of proteoglycan fragments (2,3), KS (3,4), and the carboxy-terminal peptide of type II collagen (5) are reported to be increased in joint fluid. These molecules can usually be measured by immunochemical methods.…”
mentioning
confidence: 99%
“…The role of KS as a biomarker of mechanical loading of the spine was reviewed by Kuiper et al, who concluded that ''the serum level of KS has the potential to be a biomarker of degeneration of intervertebral discs'' [22]. Mehraban et al, presenting the results of their study of patients with osteoarthritis and rheumatoid arthritis, also concluded that serum AgKS increases in the presence of cartilage degradation, but suggested the elevations do not quantitatively define the extent or duration of articular disorder [28]. The results of our longitudinal exploratory study of KS levels in the blood of patients with sciatica are compatible with the contention raised by Kuiper's group but this hypothesis clearly needs further testing.…”
Section: Discussionmentioning
confidence: 99%